The Role of Digital Transformation Strategies in Raising the Operational and Marketing Efficiency of Telecommunications Services in the Kingdom of Saudi Arabia: An Applied Study on the Saudi Telecom Company - Zahid, Amal Fareed (The Arab Journal of Administration, 2025)
The study aims to identify the role of digital transformation strategies in raising the operational and marketing efficiency of telecommunications services at the STC. The research used descriptive analytical, and the questionnaire used to collect data from members of the research sample, which was randomly selected of employees working at the STC. The selected sample (60) male and female, the results showed, that digital transformation strategies through the elements of time reduction, routine reduction, management approval, and the flexible system, have a very large role in raising the operational and marketing efficiency of the communications services of the STC. The results also showed there are difficulties of moderate degrees facing the application of digital transformation strategies in raising the operational and marketing efficiency of telecommunications services, such as the lack of training programs to develop the capabilities of workers, and there is also difficulty in using applications for all age groups, which affects the operational and marketing efficiency of the company. The study recommended maintaining the advanced stages the company has reached with regard to digital transformation in its services and working on continuous improvement in the same field, need for the company’s management to make training on digital transformation a priority that senior management should focus on or use as an effective tool for preparing competencies. Necessary to perform electronic work by providing more opportunity to use technology in digital transformation.